Kobieta u progu życia. Dojrzewanie do miłości, seksualności, przyjaźni w Kobietach Zofii Nałkowskiej - Kaźmierska, Anna (Starość i młodość w literaturze i kulturze, 2016)
The debut novel by Zofia Nałkowska, entitled Women is a work about youth and maturation to life.The author is raising the motif, which is known and worked out in the literature of many periods, but shewrites about it in an unique way. Firstly Nałkowska herself is on the threshold of life and career as a novelist.The consequences of that are the autobioghraphical signs, which are commented at the beginningof this paper. In the next paragraphs there are described the female hereos of the novel — young women, who are excited with the life and its opportunities, as well as dissappointed with the painful lessons lifegives them. This paper is trying to present the femininity “in statu nascendi” and its immaturity, naivetyand narcissism. The complicated process of maturation is described with such elements like: looking forlove, living in friendship and discovering body and people’s sexuality as well as searching for a right wayto live and think. This paper presents a lot of contrasts: naivety and arrogance, innocence and the strenghtof desire, excitment and the tendency to analyse.